PENGARUH PENGGUNAAN MOBILE BANKING TERHADAP KEPUASAN TRANSAKSI NASABAH PADA BANK MEGA CABANG PAREPARE - Setya Ningrum, Ambar; Azis, Abdul; Harun, Hernianti; Darmawan, Darmawan (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2025)
Mobile Banking is a bank service through an application on a mobile phone that facilitates transactions such as checking sado, transfers, and payments quickly and practically. Meanwhile, customer transaction satisfaction refers to the level of satisfaction felt by customers after conducting banking activities, which reflects the extent to which customer expectations are met through the services provided. This study aims to determine how much influence the use of mobile banking has on customer transaction satisfaction at Bank Mega Parepare Branch. Mobile banking is an application-based service that makes it easy for customers to carry out various transactions efficiently and flexibly. The approach used in this research is a quantitative approach, with random sampling techniques. Primary data was collected through questionnaires from 100 respondents from 1000 population who are active customers of Bank Mega. The type of data used is quantitative data analyzed using Structural Equation Modeling (SEM) method, with the help of SmartPLS software version 4. The results indicated that the use of mobile banking has a positive and significant influence on customer transaction satisfaction. This finding shows that the ease of accessing services and the flexibility of time in transactions contribute to increasing customer satisfaction.